Growth, industrial quality, and nutrient balance of sugarcane cultivars under fertilization in the Cerrado (Brazilian savanna) (Research, Society and Development, 2020)
This paper aimed to evaluate the response of sugarcane cultivar to the addition of increasing NPK doses in Oxisol, in Ceres municipality, Goiás State (GO), Brazil, in the 2018/2019 harvest. The first experiment was in completely randomized design (CRD) in 2x4x7 split-plot scheme with two cultivars (RB92579 and SP801816), four fertilizer NPK 05-25-25 doses (0, 250, 500, and 750 kg ha-1) in seven evaluation periods (every two months) with four replicates. In the experiment end-cycle, there was no period factor, setting a 2x4 fatorial arrangement, also with four replicates. The growth variables were: (a) number of tillers (NT); (b) plant height (PH); (c) culm diameter (CD); (d) number of green leaves (GL); and (e) number of buds (NB). The end-cycle variables were: (a) ton of culms per hectare (TCH); (b) °Brix; (c) apparent sucrose content in the broth (Pol); and (d) total recoverable sugars (TRS). The phosphorus (P) and potassium (K) nutrient balance in the soil and in the crops was also evaluated. The variables CD, GL and NB no showed significant interaction for cultivation x fertilization. TCH did not differ for treatments. The fertilization influenced the ºBrix, Pol, FC, and TRS. For the RB92579 cultivar, the response was linear for oBrix, Pol, and TRS. Maximum tillering occurred at 150th day after planting (DAP) in the RB92579 cultivar and was linear for SP801816 cultivar. The maximum technical efficiency of NPK 05-25-25 doses for the RB92579 and SP801816 cultivars vary from 455.6 to 750 and 442.7 to 750 kg ha-1, respectively. The RB92579 showed higher yield (9.7% - TCH) than SP801816 cultivar. Doses from 500 kg ha-1 showed a positive balance for K and P, respectively, for sugarcane plant, under this study conditions.